Examining the socioeconomic dynamics of Beta-thalassaemia screening carriers and dropouts among secondary school adolescents: a comparative study in Sabah and Sarawak - Abd Rahim, Azrin Syahida; Mohamed, Don Ismail; Zakaria, Zukarnain; Sulaiman, Lokman Hakim; Jaafar, Safurah; Abd. Rahim, Nour El Huda (Health & Medical Sciences Division of ATINER, 2025)
This study provides a novel analysis of the socioeconomic factors influencing screening dropout rates among beta-thalassemia carriers in Sabah and Sarawak, Malaysia, using 2018 data from the National Thalassemia Screening Programme. Our retrospective design focused on form four students, examining the interplay of ethnicity, locality, and gender with dropout rates. Notably, male carrier rates were higher in Sabah (49.90%) compared to females (50.10%), while Sarawak showed 51.56% for males and 48.44% for females. Gender disparities in dropout rates were particularly pronounced in Sabah, where females had double the dropout rates of males (70.62% vs. 29.38%). Extreme dropout rates were found in certain localities, namely Pitas, Sabah (47%) and Belaga, Sarawak (55%). The study highlights the substantial prevalence of thalassemia carriers among natives, with 93.9% in Sabah and 59.7% in Sarawak, underscoring the critical need for targeted, gender-sensitive screening interventions. This research contributes significantly by demonstrating the importance of precision in thalassemia screening programs to mitigate dropout rates and reduce the incidence of thalassemia births. These findings strongly advocate for early carrier identification as a strategic measure to improve educational outcomes and public health in high-risk regions.